The future of the financial exchanges insights and analysis from the Mondo Visione Exchange Forum - Skeete, Herbert C. (Elsevier and Mondo Visione world capital markets series)
An overview of the latest technological, regulatory, and market developments in the exchange industry and the common problems exchanges face; explain how these problems are being addressed; and present the consensus view from leading exchange professionals.